Lipid profiling of human diabetic myocardium reveals differences in triglyceride fatty acyl chain length and degree of saturation. (1st December 2020) - Björnson, Elias; Östlund, Ylva; Ståhlman, Marcus; Adiels, Martin; Omerovic, Elmir; Jeppsson, Anders; Borén, Jan; Levin, Malin C.
Abstract: Background: Type 2 diabetes is a major health problem in the world, and is strongly associated with impaired cardiac function and increased mortality. The causal relationship between type 2 diabetes and impaired cardiac function is still incompletely understood but changes in the cardiac lipid metabolism are believed to be a contributing factor. The objective of this study was to determine the lipid profile in human myocardial biopsies collected in vivo from patients with type 2 diabetes and compare to non-diabetic controls. Method: We conducted full lipidomics analyses, using mass spectrometry, of 85 right atrial biopsies obtained from diabetic and non-diabetic patients undergoing elective cardiac surgery. The patients were characterized clinically and serum was analyzed for lipids and biochemical markers. Results: The groups did not differ in BMI and in circulating triglycerides. We demonstrate that type 2 diabetes is associated with alterations in the cardiac lipidome. Interestingly, the absolute amount of lipids is not altered in the diabetic myocardium. However, triglycerides with longer fatty acyl chains are more abundant and there is a higher degree of unsaturated fatty acid chains in triglycerides in diabetic myocardium. Conclusions: Our study reveals that type 2 diabetes is a relatively strong determinant of the human cardiac lipidome (compared to other clinical variables). Although the total lipid content in the diabetic myocardium is not increased, the lipid composition is markedly affected. Highlights: Type 2 diabetes status correlates with variation in the human cardiac lipidome. The absolute amount of lipids is not altered in the diabetic myocardium. Triglycerides with longer fatty acyl chains are more abundant in diabetic myocardium. There is a higher degree of unsaturated fatty acid chains in triglycerides in diabetic myocardium.